2013
DOI: 10.3758/s13415-013-0194-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of alpha oscillations elucidate facial affect recognition in schizophrenia

Abstract: Impaired facial affect recognition is characteristic of schizophrenia and has been related to impaired social function, but the relevant neural mechanisms have not been fully identified. The present study sought to identify the role of oscillatory alpha activity in that deficit during the process of facial emotion recognition. Neuromagnetic brain activity was monitored while 44 schizophrenia patients and 44 healthy controls viewed 5-s videos showing human faces gradually changing from neutral to fearful or hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 95 publications
(104 reference statements)
3
25
1
Order By: Relevance
“…Recently, Lange et al (2013) found increased theta-band power in the auditory cortex during the processing of incongruent compared with congruent audiovisual speech. Interestingly, altered oscillatory responses in unisensory paradigms have been reported previously in SZP (Grützner et al 2013;Popov et al 2014Popov et al , 2015Uhlhaas and Singer 2010). For example, SZP show altered frontal thetaband power during the processing of color-word incongruence (Popov et al 2015).…”
Section: New and Noteworthymentioning
confidence: 81%
“…Recently, Lange et al (2013) found increased theta-band power in the auditory cortex during the processing of incongruent compared with congruent audiovisual speech. Interestingly, altered oscillatory responses in unisensory paradigms have been reported previously in SZP (Grützner et al 2013;Popov et al 2014Popov et al , 2015Uhlhaas and Singer 2010). For example, SZP show altered frontal thetaband power during the processing of color-word incongruence (Popov et al 2015).…”
Section: New and Noteworthymentioning
confidence: 81%
“…In addition to abnormalities of high-frequency oscillations, alterations have also been demonstrated for lower-frequencies in the theta/alpha-frequency range, during sensory processing and working memory tasks [78][79][80]. An important question is whether these abnormalities are secondary to gamma-band dysfunctions or whether they represent independent abnormalities.…”
Section: Disturbances In Neural Oscillations and E/i-balance Parametementioning
confidence: 93%
“…In the present study, FAT served to examine neural correlates of training targeting facial affect discrimination, which Popov et al (2014) found to be impaired in schizophrenia patients.…”
Section: Methodsmentioning
confidence: 99%